A model of household type specific food demand behaviour in Hungary - Stephan Brosig (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2000)
The paper describes a two stage model of Hungarian households' food demand. Demand for the food aggregate is represented by a Working-Leser type single equation model while demand for seven distinct food types is modelled in a complete demand system using the LA/AIDS functional form. Estimation is based on household budget survey data for 1996. Demand elasticities are estimated for average households as well as for specific groups defined by sociodemographic characteristics. Fruit and vegetables are found to be the food types with most elastic demand but in general, differences between elasticities for different products as well as between different sociodemographic groups are relatively small. – – Das Papier beschreibt ein Modell der Nahrungsmittelnachfrage ungarischer Privathaushalte. Die Nachfrage nach dem Gesamtaggregat "Nahrungsmittel" wird durch ein Eingleichungsmodell vom Working-Leser Typ beschrieben während die Verteilung der Nahrungsmittelausgaben auf sieben Nahrungsmitteltypen durch ein vollständiges Nachfragesystem vom Typ LA/AIDS modelliert wird. Die Datengrundlage für Parameterschätzungen entstammt den Haushaltsbudgeterhebungen des Statistischen Zentralamtes aus dem Jahr 1996. Nachfrageelastizitäten wurden sowohl für durchschnittliche Haushalte als auch für spezifische soziodemographische Bevölkerungsgruppen errechnet. Die höchsten Elastizitäten weist die Nachfrage nach Obst und nach Gemüse auf, allerdings sind die Unterschiede zwischen den Elastizitäten für verschiedene Nahrungsmitteltypen und für verschiedene Bevölkerungsgruppen relativ klein.
urn:nbn:de:gbv:3:2-22956
Keywords: D12; C31; C51; 330; food demand; demand modelling; Hungary; Nahrungsmittel; Nachfragemodell; Ungarn; Nahrungsmittelkonsum; Nachfragesystem; Schätzung; Ungarn